Characterization of the Paint from "The Lord's Transfiguration" Icon by Grigore Ranite. (22nd January 2021) - Bratu, I.; Măruţoiu, C.; Nemeş, D.; Toader, D.; Nemeş, O. F.; Suciu, R. C.
Abstract: "The Lord's Transfiguration" icon painted by Grigore Ranite belongs to a collection of altarpiece icons from the Ethnographic Museum of Transylvania. The aim of this paper is to present the results obtained from the scientific investigations carried out to establish the materials and methods used by the painter for the accomplishment of the religious art work, both for conservation and restoration purposes, as well as to enrich the knowledge about the work of this particular author and about the Transylvanian iconography in general. The analyses were performed by means of X-ray fluorescence (XRF) spectroscopy and destructive and nondestructive Fourier transform infrared (FTIR) spectroscopy.